MAKNA PENDIDIKAN NYANYIAN MASAMPER BAGI MASYARAKAT SANGIHE YANG BERADA DI TATELI MINAHASA - Geraldy F Telussa; Markus Wibowo (Clef: Jurnal Musik dan Pendidikan Musik, 2020)
Abstract This research is a study of the meaning of education found in the Masamper song, a traditional Sangihe song. The method used in this study is a qualitative method, which is a research method based on the philosophy of postpositivism. To interpret Masamper's song, this study uses the theory of discourse analysis which in the text analysis of a Masamper song uses 3 (three) aspects, namely; syntactic analysis, semantic analysis, and pragmatic analysis. Based on the data analysis, it can be stated that the Masamper song is a song that can be a means of communicating, conveying messages and advice through the song being sung, and the message delivered can be seen from the lyrics of the song to be sung. One meaning that can be conveyed is the meaning of education. The meaning of education that can be said in the meaning of Masamper's singing is inclined to the meaning of morality that can be implemented in the daily life of Sangihe people in Tateli.